Probing the Outstanding Local Hydrophobicity Increases in Peptide Sequences Induced by Incorporation of Trifluoromethylated Amino Acids. (23rd April 2018) - Gadais, Charlène; Devillers, Emmanuelle; Gasparik, Vincent; Chelain, Evelyne; Pytkowicz, Julien; Brigaud, Thierry
Abstract: In order to achieve accurate determination of the local hydrophobicity increases in peptide sequences produced by incorporation of trifluoromethylated amino acids (TfmAAs), the chromatographic hydrophobicity indexes ( ϕ 0 ) of three series of tripeptides containing three unnatural trifluoromethylated amino acids have been measured and compared with those of their non‐fluorinated analogues. The hydrophobic contribution of each fluorinated amino acid was quantified by varying the position and the protection of ( R )‐ and ( S )‐α‐trifluoromethylalanine (TfmAla), ( R )‐trifluoromethylcysteine (TfmCys), and ( S )‐trifluoromethionine (TFM) in a short peptide sequence. As a general trend, strong increases in hydrophobicity were precisely measured, even exceeding the high hydrophobic contribution of the natural amino acid isoleucine. This study validates the incorporation of trifluoromethylated amino acids into peptide sequences as a rational strategy for the fine‐tuning of hydrophobic peptide–protein interactions. Abstract : Hydrophobic effect : The incorporation into peptides of amino acids containing CF3 or SCF3 groups constitutes a powerful strategy for dramatically increasing and tuning the peptides' local hydrophobicity. Hydrophobicity indexes ( ϕ 0 ) derived from RP‐HPLC provide accurate measurements of these outstanding hydrophobicity increases.